Tracking the damages of the Shaheen cyclone in the Sultanate of Oman. Issue 12 (17th November 2022) - Ibrahim, Osama Ragab; Al-Amir, Maryam; Al-Maghawry, Salma
Abstract: The Sultanate of Oman is in the south-eastern part of the Persian Gulf. Oman's coast causes Oman to be exposed to tropical cyclones occasionally. The damages occur when hurricanes reach the land, but some hurricanes dissipate in the sea without any noticeable harm. Generally, these strong storms hit Oman every 3 or 4 years between June and October, and it is mostly in the southern part of the Sultanate. One of these cyclones was Gonu on June 1, 2007, which caused 50 deaths in total and the damaged areas cost around 4.2 billion (2007 US dollars). This paper reviews and tracks the tropical cyclone Shaheen, which hit the Omani coast on October 2, 2021. We have used the hydrological data of previous cyclones to state the level of damage the cyclone caused. As expected, the cyclone caused a lot of human and material losses in a very short period due to the inadequate flood drain systems in Al-Khaboura city. Results showed the necessity of a proper stormwater drainage system to be installed in the northern cities of Oman. These effects were followed by a 2-day holiday for both government and private sectors for the sake of people's safety. HIGHLIGHTS: Shaheen cyclone is one of the special cyclones that happened in Oman. The risks that happened are so rare. The collected data are clear and very precise. The reading of this article is enough to get the cyclone documented. Studying this type of cyclone can save humans from the next cyclones by proposing different structures for protection.